Changes in the Morphology of a Recreational Garden Settlement: The Case Study of Sokolnik - Makowska-Iskierka, Marzena (Turyzm/Tourism, 2004)
This paper examines the changes between 1987 and 2001 in the morphology (including the internal structure, spatial composition and the physiognomy of the urban fabric) of Sokolniki, a recreational settlement situated outside of Łódź, due to its tourist function.